2002
DOI: 10.1002/1522-2683(200209)23:17<2842::aid-elps2842>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Evalution of capillary electrophoresis-frontal analysis for the study of low molecular weight drug-human serum albumin interactions

Abstract: Capillary electrophoresis frontal analysis was applied to 12 low molecular weight compounds including 8 drug substances displaying a range of different properties with respect to binding affinity, binding location, structure, lipophilicity, charge at physiological pH, and electrophoretic mobility. It was found that capillary electrophoresis frontal analysis can be used as a general method to study and quantify drug-human serum albumin interactions. The binding parameters obtained were consistent with literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 64 publications
2
83
0
Order By: Relevance
“…Both warfarin and HSA are negatively charged at pH 7.4. It has been shown that the electrophoretic mobility of HSA is not changed significantly upon binding of low-molecular-weight ligands such as warfarin [34], thus, the mobility of free protein and complex can be considered to be equal. As separation progresses free warfarin, warfarin-HSA complex, and HSA are swept towards the detector by the EOF.…”
Section: Principles Of Capillary Electrophoresisfrontal Analysis (Ce-fa)mentioning
confidence: 78%
See 3 more Smart Citations
“…Both warfarin and HSA are negatively charged at pH 7.4. It has been shown that the electrophoretic mobility of HSA is not changed significantly upon binding of low-molecular-weight ligands such as warfarin [34], thus, the mobility of free protein and complex can be considered to be equal. As separation progresses free warfarin, warfarin-HSA complex, and HSA are swept towards the detector by the EOF.…”
Section: Principles Of Capillary Electrophoresisfrontal Analysis (Ce-fa)mentioning
confidence: 78%
“…Otherwise determination of the free ligand concentrations is not feasible. In the case above, the mobility of warfarin changes upon binding while that of HSA is unchanged [34]. Recently, we have addressed the necessity of having plateau peak conditions in CE-FA experiments (Østergaard and Hansen, manuscript in preparation).…”
Section: Requirements For Using Ce-famentioning
confidence: 85%
See 2 more Smart Citations
“…50 We elected to evaluate the impact of treating bile duct-cannulated rodents with sodium benzoate to displace any chelator potentially bound to Sudlow type I and II albumin binding sites. 50 Five experiments were carried out (Table 4). Rodents were given (i) sodium benzoate dissolved in distilled water at 250 mg/kg/dose sc times six doses, (ii) (S)-4′-(HO)-DADFT (1) po at 300 μmol/kg, (iii) 1 given po at 300 μmol/kg plus sodium benzoate (250 mg/kg/dose).…”
Section: The Possible Impact Of Ligand-albumin Binding On Icementioning
confidence: 99%